La tutela judicial efectiva en clave juslaboralista en Cuba - Fernández Toledo, Aymee (Pontificia Universidad Católica del Perú, 2025)
In 2019, the Cuban legal system was shaken by the introduction of a new Constitution which, among other essential transformations, enshrined judicial guarantees of rights. Effective judicial protection made its way into the national legal debate. The judicial and procedural reform of 2021 contributed substantially to this. However, the delimitation of its content is still a pending task. Theoretical studies have much to offer in order to fill this gap. Interpreters, and especially the courts, will have to find in them a solid basis that will allow them to shape its extension. For labour rights, which are particularly imbued with an essential tutelary character, such a task must be complemented by the examination of principles and the way in which they shape procedural institutions and categories. This is the perspective presented in this text, which reflects on the current means of settling labour disputes, with the sole ambition of fertilising the path.

En 2019, el ordenamiento jurídico cubano se vio estremecido por la irrupción de una nueva Constitución que, entre otras transformaciones esenciales, consagró las garantías jurisdiccionales de los derechos. La tutela judicial efectiva se abrió paso en el debate jurídico nacional. A ello contribuyó, sustancialmente, la reforma judicial y procesal de 2021. No obstante, la delimitación de su contenido aún es tarea pendiente. Mucho pueden aportar los estudios teóricos para colmar ese vacío. En ellos, habrán de encontrar los intérpretes, en especial, los tribunales un sólido asidero que les permita configurar su extensión. Para los derechos del trabajo, particularmente imbuidos de una esencia tutelar, tal cometido ha de complementarse con el examen de los principios y la forma en que ellos modulan las instituciones y categorías procesales. La perspectiva que presenta este texto reflexiona acerca de los actuales medios de solución de los conflictos laborales, con la única ambición de fertilizar el camino.
The effective judicial protection in a juslaboralist perspective in Cuba
Keywords: Effective judicial protection; Labour rights; Labor law principles; Solution of work conflicts; Administration of justice; Labour justice; Labor Law; Cuba; Tutela judicial efectiva; Derechos del trabajo; Principios del Derecho del trabajo; Solución de conflictos laborales; Impartición de justicia; Justicia laboral; Derecho Laboral; Cuba; https://purl.org/pe-repo/ocde/ford#5.05.00